Implications of impaired endurance performance following single bouts of resistance training: An alternate concurrent training perspective - Doma, K.; Deakin, G. B.; Bentley, D. J. (Sports Medicine, 2017)
A single bout of resistance training induces residual fatigue, which may impair performance during subsequent endurance training if inadequate recovery is allowed. From a concurrent training standpoint, such carry-over effects of fatigue from a resistance training session may impair the quality of a subsequent endurance training session for several hours to days with inadequate recovery. The proposed mechanisms of this phenomenon include: (1) impaired neural recruitment patterns; (2) reduced movement efficiency due to alteration in kinematics during endurance exercise and increased energy expenditure; (3) increased muscle soreness; and (4) reduced muscle glycogen. If endurance training quality is consistently compromised during the course of a specific concurrent training program, optimal endurance development may be limited. Whilst the link between acute responses of training and subsequent training adaptation has not been fully established, there is some evidence suggesting that cumulative effects of fatigue may contribute to limiting optimal endurance development. Thus, the current review will (1) explore cross-sectional studies that have reported impaired endurance performance following a single, or multiple bouts, of resistance training; (2) identify the potential impact of fatigue on chronic endurance development; (3) describe the implications of fatigue on the quality of endurance training sessions during concurrent training, and (4) explain the mechanisms contributing to resistance training-induced attenuation on endurance performance from neurological, biomechanical and metabolic standpoints. Increasing the awareness of resistance training-induced fatigue may encourage coaches to consider modulating concurrent training variables (e.g., order of training mode, between-mode recovery period, training intensity, etc.) to limit the carry-over effects of fatigue from resistance to endurance training sessions.